THE ROLE OF DIGITAL LITERACY AND TECHNOLOGY ADOPTION IN FACILITATING SOCIAL TRANSFORMATION IN AFGHANISTAN - Hakimi, Musawer; Sediqi, Mateeullah; Kohistani, Ahmad Jamy; Quraishi, Tamann (Universitas Pendidikan Nasional, 2025)
In Afghanistan, the rate of technological development is balanced by the challenges of digital literacy due to sociopolitical instability, the lack of infrastructure, and educational disparities. This research not only examined the landscape of digital literacy and technology use for Afghan adults, but also the challenges and opportunities around using technology. A quantitative cross-sectional design was employed and data were collected from 300 individuals aged 18 and older, representing urban and rural areas. Demographic representation was assured through purposive sampling by gender, age, education, and occupation. Data to assess participants digital skills, technology use, and perceived barriers to digital literacy and technology were collected through a five-point Likert scale questionnaire which relied on previously validated digital literacy frameworks. The participants completed the survey questions either face-to- face as part of an interview, or an online survey available in Dari and Pashto. The findings indicate that there are considerable gaps in access to, and skills to use, digital technologies, especially for rural and lesser educated groups, and identify distance and as a consequence reinforcing the digital divide in Afghanistan.This study fills a major gap in the research literature on digital literacies and provides an empirical study from a conflict-affected country such as Afghanistan, which is one of the few on this topic. This study also provides insights into complex links between sociopolitical instability and gender inequities and educational impediments to digital exclusion. The study underscores the need for improved access to technology and infrastructure as key factors in digital literacy initiatives. By presenting data-driven evidence from Afghanistan, this research adds a critical perspective to global digital literacy discussions, serving as a model for similar contexts. Policymakers and development organizations can use these findings to close digital divides and foster long-term digital empowerment in Afghanistan.